Inhibition of aryl hydrocarbon receptor signaling promotes the terminal differentiation of human erythroblasts. (11th January 2022) - Chen, Yijin; Dong, Yong; Lu, Xulin; Li, Wanjing; Zhang, Yimeng; Mao, Bin; Pan, Xu; Li, Xiaohong; Zhou, Ya; An, Quanming; Xie, Fangxin; Wang, Shihui; et al.
Abstract: The aryl hydrocarbon receptor (AHR) plays an important role during mammalian embryo development. Inhibition of AHR signaling promotes the development of hematopoietic stem/progenitor cells. AHR also regulates the functional maturation of blood cells, such as T cells and megakaryocytes. However, little is known about the role of AHR modulation during the development of erythroid cells. In this study, we used the AHR antagonist StemRegenin 1 (SR1) and the AHR agonist 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin during different stages of human erythropoiesis to elucidate the function of AHR. We found that antagonizing AHR signaling improved the production of human embryonic stem cell derived erythrocytes and enhanced erythroid terminal differentiation. RNA sequencing showed that SR1 treatment of proerythroblasts upregulated the expression of erythrocyte differentiation-related genes and downregulated actin organization-associated genes. We found that SR1 accelerated F-actin remodeling in terminally differentiated erythrocytes, favoring their maturation of the cytoskeleton and enucleation. We demonstrated that the effects of AHR inhibition on erythroid maturation were associated with F-actin remodeling. Our findings help uncover the mechanism for AHR-mediated human erythroid cell differentiation. We also provide a new approach toward the large-scale production of functionally mature human pluripotent stem cell-derived erythrocytes for use in translational applications.